Clinical evaluation of Sofia Rapid Antigen Assay for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among emergency department to hospital admissions. (24th August 2022) - Smith, Richard D.; Johnson, J. Kristie; Clay, Colleen; Girio-Herrera, Leo; Stevens, Diane; Abraham, Michael; Zimand, Paul; Ahlman, Mark; Gimigliano, Sheri; Zhao, Richard; Hildenbrand, Cynthia; Barrueto, Fermin; et al.
Abstract: Objective: To determine the utility of the Sofia SARS rapid antigen fluorescent immunoassay (FIA) to guide hospital-bed placement of patients being admitted through the emergency department (ED). Design: Cross-sectional analysis of a clinical quality improvement study. Setting: This study was conducted in 2 community hospitals in Maryland from September 21, 2020, to December 3, 2020. In total, 2, 887 patients simultaneously received the Sofia SARS rapid antigen FIA and SARS-CoV-2 RT-PCR assays on admission through the ED. Methods: Rapid antigen results and symptom assessment guided initial patient placement while confirmatory RT-PCR was pending. The sensitivity, specificity, positive predictive values, and negative predictive values of the rapid antigen assay were calculated relative to RT-PCR, overall and separately for symptomatic and asymptomatic patients. Assay sensitivity was compared to RT-PCR cycle threshold (Ct) values. Assay turnaround times were compared. Clinical characteristics of RT-PCR–positive patients and potential exposures from false-negative antigen assays were evaluated. Results: For all patients, overall agreement was 97.9%; sensitivity was 76.6% (95% confidence interval [CI], 71%–82%), and specificity was 99.7% (95% CI, 99%–100%). We detected no differences in performance between asymptomatic and symptomatic individuals. As RT-PCR Ct increased, the sensitivity of the antigen assay decreased. The mean turnaround time for the antigen assay was 1.2 hours (95% CI, 1.0–1.3) and for RT-PCR it was 20.1 hours (95% CI, 18.9–40.3) ( P < .001). No transmission from antigen-negative/RT-PCR–positive patients was identified. Conclusions: Although not a replacement for RT-PCR for detection of all SARS-CoV-2 infections, the Sofia SARS antigen FIA has clinical utility for potential initial timely patient placement.